Skin autofluorescence as an indicator of advanced glycation end-product accumulation in the prognosis of age-related cardiovascular disease: literature review - Petr A. Lebedev; Naila A. Davydova; Elena V. Paranina; Maria A. Skuratova (КардиоСоматика, 2023)
Advanced glycation end products (AGEs) are represented by heterogeneous molecular structures and their accumulation in organs and tissues reflects the intensity of oxidative stress and glycemia. As a physiological process, aging is associated with AGE accumulation and changing the morphology and functions of the vascular wall. Accelerated AGE accumulation initiates inflammation, contributing to the development of cardiovascular diseases, such as arterial hypertension, coronary heart diseases, and atherosclerosis of peripheral arteries; conditions associated with high cardiovascular risks such as prediabetes, diabetes mellitus type 2, and chronic kidney diseases are also characterized by the accelerated AGEs accumulation. The ability of AGEs to fluorescence underlies noninvasively in blood serum, tissues, and skin using a well-proven technique of autofluorescence, which is little known to domestic specialists. This review presents the possibilities of autofluorescence to reflect arterial wall remodeling, which includes stiffness, vascular endothelial function, atherosclerotic plaque formation, and instability, using modern materials. The review emphasizes the evidence base regarding the ability of this method to predict mortality and cardiovascular events in a large population from low to high risk.